Association between plain water intake and the risk of osteoporosis among middle-aged and elderly people in the United States: a cross-sectional study - Wang, Xudong; Wang, Meng; Guo, Zijian; Xiang, Chuan (Frontiers in Nutrition, 2025)
BackgroundThe connection between plain water intake (PWI) and osteoporosis risk is still unclear. The investigation aimed to identify the relationship between PWI and osteoporosis risk in middle-aged and elderly individuals in the United States (US).MethodsThis cross-sectional study was conducted among participants aged 50 years and older in the following waves of the National Health and Nutrition Examination Survey (NHANES): 2007–2008, 2009–2010, 2013–2014, and 2017–2018. The relationship between PWI and osteoporosis risk was examined by multivariable logistic regression models, accompanied by subgroup analyses and interaction tests. Smooth curve fitting and threshold effect analysis were utilized.ResultsThe present investigation included 6,686 participants. In accordance with the fully adjusted model, individuals in the highest PWI tertile had a significantly reduced risk of osteoporosis in contrast to those in the lowest tertile [odds ratio (OR) = 0.62; 95% confidence interval (CI): 0.49–0.77; P for trend<0.001]. After adjusting for all covariates, a higher PWI was linked to a decreased risk of osteoporosis (OR = 0.92; 95% CI: 0.86–0.98; p = 0.008). No significant interactions were detected in the subgroup analyses for age, gender, race, body mass index, diabetic history, hypertension status, smoking history, consumption of prednisone or cortisone, or moderate or strenuous activity (all P for interaction>0.05). Smooth curve fitting and threshold effect analysis revealed that when PWI was less than 1,220 mL/day, there was a significant negative connection between PWI and osteoporosis risk (OR = 0.79; 95% CI: 0.70–0.89; p < 0.001); nevertheless that association was not significant when PWI was greater than 1,220 mL/day (OR = 1.06; 95% CI: 0.95–1.17; p = 0.288).ConclusionThe outcomes of our investigation indicated that among middle-aged and older US adults, a higher PWI was connected with a moderately reduced osteoporosis risk. Managing PWI might reduce the osteoporosis risk.